AI-Driven Automation in Cyber Incident Response: Key Challenges, Opportunities, and Future Directions - Amol Sharadchandra Chaudhari (International Journal of Intelligent Systems and Applications in Engineering, 2020)
Cyber threats are becoming more common and more complex, therefore we need faster and smarter ways to respond to them. This study looked into the function of Artificial Intelligence (AI) in automating the response to cyber incidents, focusing on how well it works, what problems it might face, and what opportunities it might create. A mixed-methods approach was used, which included testing how well AI-based tools worked in fake cyber-attack situations and talking to cybersecurity experts. The results showed that AI tools cut down on detection and response times by a lot while still being quite accurate at finding and stopping threats. However, concerns regarding trust, explainability, and integration with legacy systems emerged as key barriers to adoption. The results imply that AI has the ability to change cybersecurity for the better, but it won't be successful unless systems that are clear and easy to understand are made that can work with human experience. These insights are very helpful for companies who want to use AI to improve their ability to respond to incidents.